Analysis Of The i-Care Application On National Health Insurance Patient Satisfaction At Pratama Marga Ayu Clinic - Rai Riska Resty Wasita (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2024)
Background: The Social Security Administering Agency (BPJS) for Healthh as the organizer has developed an information technology system-based application in the form of the i-Care application. This new breakthrough is expected to make it easier for users to view the health service history of service users at health facilities online. The i-Care application has been implemented since early 2023 and while using this application no evaluation has been carried out to determine the level of satisfaction of JKN participants using i-Care. Objectives: The aim of the research is to analyze the use of the i-Care application on National Health Insurance patient satisfaction at the Marga Ayu Clinic. Research Metodes: This research is a quantitative analytical research with a cross sectional approach where sample selection was carried out using the role of thumb of 50 JKN participants. Data collection was carried out by distributing questionnaires referring to the EUCS method. The questions were divided into 5 categories, namely: content, accuracy, format, ease of use, timeliness and user satisfaction. The analysis test used the Spearman Rank test to find out the correlation between the use of the i-Care application and the satisfaction of National Health Insurance patients at the Marga Ayu Clinic. Results: The research results show that there is a significant, positive and strong relationship between the variables content (0.000<0.05), accuracy (0.005<0.05), format (0.017<0.05), ease of use (0.001<0.5) and timeliness (0.003<0.05) on i-Care user satisfaction. Conclusion: There is a significant, positive and strong relationship between content, format, ease of use, timeliness and i-Care user satisfaction. However, the accuracy variable is not related to satisfaction with a sig value of 0.434 (>0.005). This is because there is still data or information that is not updated enough and sometimes errors occur in the application.